Tradição, razão e verdade na Filosofia Moral de Alasdair MacIntyre - Damasceno, Márcia Marques (2010)
This master dissertation addresses the theory of the rationality of traditions proposed by Alasdair MacIntyre. He advocated a type of moral philosophy grounded on the investigation of the rationality implicit in the practices of moral traditions. In addition to this, he defended the superiority of the Aristotelian moral philosophy in the history of moral theories and favored a form of Thomism. This work is intended to show that the theory of truth as correspondence that MacIntyre attached to his moral theory has some metaphysical implications that are at odds with the premises of his moral investigation.